Determinan Status Vaksinasi Covid 19 Masyarakat Di Wilayah Kerja Puskesmas Walantaka Kota Serang Provinsi Banteh Tahun 2023 - Saanah, Saanah; Utami, Sri; Ulfa, Laila (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
The Covid 19 vaccination is still a matter of pros and cons in society, giving rise to doubts among them about being able to receive it. including the effectiveness of the vaccine itself. Education and support from the family greatly influences a person's ability to receive the Covid 19 vaccination. This research aims to determine the determinants of the Covid 19 vaccination status of the community in the Walantaka Health Center working area, Serang City, Banteh Province in 2023. The method uses quantitative research with a cross sectional approach. The sample in this study used a two-proportion difference hypothesis test formula with the minimum number of samples obtained being multiplied by two to 146. The research instrument was a questionnaire. Hypothesis testing used a multiple logistic regression test. The results of the bivariate analysis showed a significant relationship between education, knowledge, attitudes and family support and Covid 19 vaccination coverage. Meanwhile, those that were not related were the variables age and beliefs. Multivariate analysis shows that family support is the dominant variable in Covid 19 vaccination coverage. Conclusions and Suggestions. Most respondents took the vaccine twice, because they were of a non-vulnerable age, low education and knowledge, beliefs, negative attitudes and received family support for the Covid 19 vaccine. There is a significant relationship between knowledge, attitudes and family support and Covid 19 vaccination coverage. Family support is the most dominant and has a 6,781 times chance of successful Covid 19 vaccination coverage compared to those who do not receive support. It is hoped that the Community Health Center can provide education and understanding about Covid 19 vaccination, either through individual, family, group and community outreach, as well as encouraging the public to maintain health protocols not only to reduce the possibility of contracting Covid 19 but also other infectious diseases. Keywords: Vaccine coverage, Knowledge, Attitude, Family support.